Indigenous Knowledge Systems and Medicinal Plant Practices among the Amppipal Community of Gorkha, Nepal - Pokharel, Saroj; Acharya, Chiranjivi; Dahal, Shree Ram (Journal of Tikapur Multiple Campus, 2026)
This paper focuses on the case study of the Amppipal community of Gorkha, Nepal and the community's indigenous knowledge systems (IKS) relating to the ethnomedicine of the community and the socio-cultural identity the community has of itself with the Amppipal socio-cultural identity as ethnomedicine. Primary health care herbal medicine practiced in the community has a unique socio-cultural order. The aims of the research are to understand the depth and breadth of the community's primary health care herbal medicine and local systems of healing and the social history of the community's knowledge systems and how they have transformed over time. The community's elders and traditional practitioners are the primary sources of knowledge the researcher has captured through semi-structured interviews and participatory observation. The research leads to the conclusion that the Amppipal herbal medicine community is in a unique state of crisis. There is a considerable body of knowledge and still the community, Amppipal, the community herbal medicine practitioners and the Amppipal herbal medicine community, is in a unique state of socio-cultural crisis because of the traditional concept and practice system of the Amppipal herbal medicine community being disrupted and permeated by the modern system of biomedicine The research recommends that a system of education that focuses on the community be created, along with a system of documentation concerning the community and the practices of its community members.